VARIETY OF RHETORICS IN POLITICAL SPEECH PRESIDENT OF THE REPUBLIC OF INDONESIA SUSILO BAMBANG YUDHOYONO AND JOKO WIDODO IN EDUCATIONAL FIELD - Noermanzah Noermanzah; Emzir Emzir; Ninuk Lustyantie (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2017)
The study aims to provide an understanding of the range of rhetoric in the political speech of the President of Indonesian Republic Susilo Bambang Yudhoyono and Joko Widodo, especially in the field of education. The research method used is the critical discourse analysis method of Norman Fairclough model. Data collection techniques used are documentation techniques, note-taking techniques, and interviews. Data analysis techniques are operated by connecting micro, meso, and macro elements in dimensions, such as: (a) text, (b) discourse practice, and (b) socio-cultural practices. The result of the research shows the rhetoric in the political speech of President Susilo Bambang Yudhoyono and Joko Widodo in the field of education which are compiled by the staf of presidential documents are as followed: 54,25% of the argumentation, 31,21% of the hortatory variety, 5,32% of the exposition, 4,25% of persuasion, 2,48% of informative variety, 1,06 % of narrative range, 0,71% of descriptive variation, 0,35% of dramatic variation, and 0,35% of procedural variation. The variety of rhetoric used aims to deliver educational programs that have been made, promises, and wishes or expectations to improve the quality of education in Indonesia, especially in the reform era.Keywords: variety of rhetoric, state speech, educationRAGAM RETORIKA DALAM PIDATO KENEGARAAN PRESIDEN REPUBLIK INDONESIA SUSILO BAMBANG YUDHOYONO DAN JOKO WIDODO PADA BIDANG PENDIDIKAN AbstrakPenelitian ini bertujuan memberikan pemahaman tentang ragam retorika dalam pidato kenegaraan Presiden Republik Indonesia Susilo Bambang Yudhoyono dan Joko Widodo khususnya dalam bidang pendidikan. Metode penelitian menggunakan metode analisis wacana kritis model Norman Fairclough. Teknik pengumpulan data menggunakan teknik dokumentasi, teknik catat, dan wawancara. Teknik analisis data dengan cara menghubungkan unsur mikro, meso, dan makro pada dimensi: (a) teks, (b) praktik wacana, dan (b) praktik sosial budaya. Hasil penelitian menunjukkan ragam retorika yang terdapat dalam pidato kenegaraan Presiden Susilo Bambang Yudhoyono dan Joko Widodo dalam bidang pendidikan yang disusun bersama tim kerjanya, yaitu ragam argumentasi terdapat 54,25%, ragam hortatori terdapat 31,21%, ragam eksposisi terdapat 5,32%, ragam persuasi terdapat 4,25%, ragam informatif terdapat 2,48%, ragam narasi terdapat 1,06%, ragam deskriptif terdapat 0,71%, ragam dramatik terdapat 0,35%, dan ragam prosedural terdapat 0,35%. Ragam retorika yang digunakan bertujuan untuk menyampaikan program pendidikan yang telah dilakukan, janji, dan keinginan atau harapan untuk memperbaiki mutu pendidikan di Indonesia khususnya pada era reformasi.Kata kunci: ragam retorika, pidato kenegaraan, bidang pendidikan